Enhancing experiential learning in manufacturing engineering technology courses: A case study of TVET education in Malaysia Technical University Network (MTUN) - Kartina, Johan; Noraini, Mohd Razali; Faiz, Mohd Turan (Springer, 2025)
Teaching engineering effectively in technology programs requires more than just academic excellence; it depends heavily on the engagement between students and their lecturers, guided by Engaged Scholarship (ES) principles. This engagement, though intangible and hard to measure, plays a critical role in creating a collaborative and interactive classroom environment. Even the best teaching plans may fall short if they aren't delivered in a way that fosters experiential learning, especially for students eager to gain practical, real-world industrial experience. This paper explores how student engagement with lecturers and the subject matter influences experiential learning in TVET (Technical and Vocational Education and Training) education. The study focused on key attributes that are crucial in TVET, using a quantitative research approach and a structured survey to gauge student engagement. Our study targeted engineering students in Malaysia Technology University Network (MTUN). The analysis of the data, using numerical scores and relative importance values, revealed that students displayed high levels of engagement (measured as Engagement Value, or EV) across all attributes of experiential learning. This high engagement was strongly linked to the lecturer's industry experience, which is a central element of the teaching framework. The results underscore the positive impact of this teaching framework, which not only enhances experiential learning but also prepares students to be job-ready—a key objective for MTUN universities in Malaysia.